2019
DOI: 10.1111/jfpp.14073
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect of ultrasound and microwave on the physical, chemical, textural, and microstructural properties of vacuum fried Chinese yam ( Dioscorea polystachya )

Abstract: Both the ultrasound and microwave are emerging technology, used for enhancement of heat and mass transfer, due to their cheap, simple, and energy saving characteristics. The combined effect of ultrasound and microwave on vacuum frying of Chinese yam at various power levels were investigated. The trends of moisture removal and oil uptake were analyzed at different power combinations of ultrasound (300 and 600 W) and microwave (1,800, 2,400, and 3,000 W). The frying time was reduced from 18 to 12 m and oil uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…In comparison to the conventionally fried (175°C ± 5°C) product, pear chips obtained under vacuum frying showed a * values to be always on the lower side (Table 3 ) reiterating the advantage of vacuum frying over conventional frying. A similar observation was made during the vacuum frying of banana and Chinese yam when an improvement in color retention (lower a * value) was recorded (Chitrakar, Zhang, & Fan, 2019; Udomkun & Innawong, 2018). It may also be noted that vacuum frying resulted in lower oil uptake when compared to conventional frying.…”
Section: Resultssupporting
confidence: 73%
“…In comparison to the conventionally fried (175°C ± 5°C) product, pear chips obtained under vacuum frying showed a * values to be always on the lower side (Table 3 ) reiterating the advantage of vacuum frying over conventional frying. A similar observation was made during the vacuum frying of banana and Chinese yam when an improvement in color retention (lower a * value) was recorded (Chitrakar, Zhang, & Fan, 2019; Udomkun & Innawong, 2018). It may also be noted that vacuum frying resulted in lower oil uptake when compared to conventional frying.…”
Section: Resultssupporting
confidence: 73%
“…Moreover, it can be seen from Table 3 that the VF+MWH led to significantly lower (P < 0.05) oil content compared to VF and P+VF. Related results were reported by Chitrakar et al (2019). The researcher concluded that the highest microwave power level led to more rapid heating, reduced frying time, increased rate of dehydration and minimised oil absorption.…”
Section: Oil Content Of the Productsmentioning
confidence: 57%
“…Related results were reported by Chitrakar et al . (2019). The researcher concluded that the highest microwave power level led to more rapid heating, reduced frying time, increased rate of dehydration and minimised oil absorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations